KEBIJAKAN KRIMINAL DALAM MENGHADAPI PERKEMBANGAN KEJAHATAN CYBER ADULTERY - Swardhana, Gde Made (TANJUNGPURA LAW JOURNAL, 2017)
Cyber crime is one of the new forms or dimensions of today's crimes gaining wide attention in the international world. One of the most disturbing issues and received the attention of various circles is the problem of cyber crime in the field of decency which became known as adultery cyber. The story of cyber adultery is essentially no different from evil / morality in the end, such as adultery. Cyber adultery / cyber sex can be seen as virtual gratification associated with sexual expression, and a new form of intimacy (a new kind of intimacy). Such intimacy or intimacy can also mean sexual intercourse or adultery. This means cyber sex is a new form of adultery. To overcome thisproblem, honesty is needed in the effort to overcome crime which is essentially an integral part of social defense and community prosperity.